Such a quiet place [compact disc, unabridged] : a novel - Miranda, Megan (Simon & Schuster Audio, 2021)
Welcome to Hollow's Edge. A private and idyllic neighborhood, one where neighbors know each other, celebrate graduation and holiday parties together, and look out for one another. But after the sudden deaths of Brandon and Fiona Truett, there's another version of Hollow's Edge, simmering underneath. One where everyone is trapped with each other, suffocated by their trial testimonies, their versions of the facts. And now, the woman they put away for the crime is back. Nearly a year earlier, Ruby Fletcher was convicted of killing Brandon and Fiona Truett by carbon monoxide poisoning. Neighbors had testified, calling her a grifter, a thief, a sociopath. Now, with her conviction overturned, Ruby is back at Hollow's Edge as if nothing has happened. When she waltzes into the home where she once lived with Harper Nash, Harper is shocked. And afraid. What does Ruby want? And more importantly, why would she possibly return to a place filled with the people who accused her?